Materials degradation mechanisms in an open cathode low power PEM Fuel Cell - Rangel, C. M. (2012)
In this work, a low power PEM fuel cell intended for passive management of water was operated integrating a range of relative humidity (RH) from 30 to 80% and temperatures from 5 to 55ºC. An open air cathode, provided with an excess air stoichiometry condition, was designed for easy water removal and stack cooling. The 4 cell stack was fed with pure hydrogen and uses own design flow field drawn on graphite plates from Schunk and a commercial MEA with carbon supported catalyst containing 0.3 mgcm-2 Pt. Full stack characterization was made using a purpose-built test station and a climatic chamber with temperature and RH control. Results indicated that 60% RH is associated to maximum performance on the fuel cell under study over the studied temperature range. While water management is done in a passive fashion, heat management is accomplished on the basis of the injection of air at the cathode with the fuel cell showing good performances at relatively low currents where back diffusion towards the anode is favored.